Pendidikan Nilai Karakter Religiositas Anak Usia Dini - Aumar, Suyanee; Jatmikowati, Tri Endang; Rachman, Angraeny Unedia (Jurnal Pendidikan Anak Usia Dini, 2023)
This study is an educational analysis aimed at shaping the attitudes and behavior of children to become good and morally upright individuals. The purpose of this research is to understand the implementation of religious character values for early childhood in PAUD Yasmin, Jember Regency. The research is of a qualitative descriptive type and employs data collection techniques such as observation, interviews, and documentation. The research findings regarding the implementation of religious character values for young children by teachers in the learning activities include the use of visual media, videos, and storytelling. In the application of religious character values for the early childhood group, this is achieved through daily routines such as Dhuha prayers, reciting prayers, memorizing short verses, and Quranic recitation. For the Playgroup age group, the application of religious character values is also carried out through daily routines, including Dhuha prayers, memorizing short verses, and reciting prayers. In the case of the Islamic Education Group (TPA), this is done through daily routines involving reciting prayers, memorizing short verses, and singing Islamic children's songs. In conclusion, the implementation of religious character values for young children can be integrated into the learning activities and further developed through self-improvement and character building for young children in their daily lives.